Delimitação do conceito de floresta nas esferas legislativa, administrativa e judicial : a necessidade de adequação do conteúdo a luz do princípio da integridade ecológica - Silva, André Luiz Falquetti e (2019)
This dissertation sought to analyze the quality and relevance of the concept of the term forest in laws, treaties and regulations applied to the environment, where the general law has not defined it, even though made it clear that forests are distinct from other forms of vegetation, focusing on them exclusive rules. In view of the constant increases in the levels of forest degradation and deforestation, such as the Atlantic Forest and the amazon rainforest, the research seeks to ensure that the definition of the term forest in the general law could contribute to their conservation. Currently, the United Nations (UN) adopts two different concepts of forest that do not converge on the same path. Accordingly to the concept Brazil adopts, the results of the quantitative of forests may change. The effects of this choice may represent a lower rate of carbon emissions from deforestation or greater availability of carbon credits. To improve the understanding of the subject, a brief introduction to the linguistic sciences was necessary, with emphasis in Terminology, which made it possible to verify the various elements that can make up a concept and the impossibility of covering all of them in a single one. Thus, according to the political moment, records of significance can be made, directly reflecting in institutes such as the legal reserve and the forest replenishment. Given the need of the Government to make choices about what the country means by forests, the Union plays a fundamental role, since it can bring uniformity, thus avoiding the proliferation of state concepts that are not aligned with the protection of this good of general interest. In addition, the concept of forest, established by the general law of the Union, could guide the Judiciary in the application of its blank criminal types. The problems in Environmental Law are usually transboundary, surpassing even the legislative needs, therefore, it is imperative that the choices made by the legislator or the administrator be based on scientific understandings of other sciences. If Brazil chooses to propose its own concept for forest, considering its needs and particularities, the precepts of ecological integrity must be incorporated to ensure the maintenance and development of forest ecosystems. Thus, the country can prevent the loss of forest biomes through savannization, as well as prevent the worsening of the global climate crisis. Finally, we present a concept which aims at the protection of biodiversity and to cover other types of vegetation that can be found in the area of uncertainty in the non-legal sciences. As the political moment is not conducive to legislative acts in the environmental area, the option for judicial control of legislative and regulatory acts represents an important tool in the protection of forests. To support the arguments pointed out throughout the text, the research has an interdisciplinary bibliographic profile, guided by the deductive method.